Implementation of Educational Support and Its’ Related Factors Associated with Random Blood Sugar among Type 2 Diabetes Mellitus Patients During Covid-19 Pandemic - Ernawati; Dewiyanti; Suardi Suardi; Dina Oktaviana (International Journal of Nursing and Health Services (IJNHS), 2021)
Background: Effective strategies in preventing type 2 diabetes mellitus and complications such as educational support, multidisciplinary management, strict monitoring, and prevention such as foot care; Objective: This study aimed to determine the relationship between the implementation of the educational support and its’ related factor with random blood sugar control in type 2 Diabetes Mellitus patients during the Covid-19 Pandemic.  Method: The retrospective cohort was applied in this study. The sampling technique in this study was non-probability sampling with a purposive sampling approach, and the number of samples in this study was 40 people. Results: There is a relationship between the implementation of educational support and random blood sugar control with ?=0.007 an OR value of 9,67, there is a relationship between age and random blood sugar control with ?=0.017 an OR value of 9,0; there is a relationship between the length of suffering from DM and random blood sugar control with ?=0.018 an OR value of 7,0; there is no relationship between obesity and random blood sugar control with ?=1.000 an OR value of 1,0, and there is no relationship between genetic and random blood sugar control with ?=0.479 an OR value of 1,8. Conclusion there is a relationship between the implementation of educative support, age, and length of suffering from diabetes mellitus with random blood sugar control